Motivation to Seek Knowledge According to the Teachings of the Prophet's Hadith - Nur Fanniyah; Mohammad Fattah (Penerbit Hellow Pustaka, 2026)
Islam places great emphasis on the pursuit of knowledge. The encouragement of learning emphasizes not only the acquisition of knowledge, but also the importance of supporting factors that can enhance one's enthusiasm for learning. One influential factor in this process is motivation. Motivation can be understood as the drive that moves a person to take a particular action. In the context of education, motivation plays a role as a force that drives individuals to continue learning and self-development.